A 3D Fractional-Order Chaotic System with Only One Stable Equilibrium and Controlling Chaos. (5th July 2017) - Shen, Shiyun; Ke, Meihua; Zhou, Ping
Abstract : One 3D fractional-order chaotic system with only one locally asymptotically stable equilibrium is reported. To verify the chaoticity, the maximum Lyapunov exponent (MAXLE) with respect to the fractional-order and chaotic attractors are obtained by numerical calculation for this system. Furthermore, by linear scalar controller consisting of a single state variable, one control scheme for stabilization of the 3D fractional-order chaotic system is suggested. The numerical simulations show the feasibility of the control scheme.